Burden of comorbid conditions in children and young people with juvenile idiopathic arthritis: a collaborative analysis of 3 JIA registries. (6th October 2021) - Kearsley-Fleet, Lianne; Klotsche, Jens; van Straalen, Joeri W; Costello, Wendy; D'Angelo, Gianfranco; Giancane, Gabriella; Horneff, Gerd; Klein, Ariane; Láday, Matilda; Lunt, Mark; de Roock, Sytze; Ruperto, Nicolino; et al.
Abstract: Objectives: Burden of comorbidities are largely unknown in JIA. From 2000, national and international patient registries were established to monitor biologic treatment, disease activity and adverse events in patients with JIA. The aim of this analysis was to investigate in parallel, for the first time, three of the largest JIA registries in Europe/internationally—UK JIA Biologic Registers (BCRD/BSPAR-ETN), German biologic registers (BiKeR/JuMBO), multinational Pharmachild—to quantify the occurrence of selected comorbidities in patients with JIA. Methods: Information on which data the registers collect were compared. Patient characteristics and levels of comorbidity were presented, focussing on four key conditions: uveitis, MAS, varicella, and history of tuberculosis. Incidence rates of these on MTX/biologic therapy were determined. Results: 8066 patients were registered into the three JIA registers with similar history of the four comorbidities across the studies; however, varicella vaccination coverage was higher in Germany (56%) vs UK/Pharmachild (16%/13%). At final follow-up, prevalence of varicella infection was lower in Germany (15%) vs UK/Pharmachild (37%/50%). Prevalence of TB (0.1–1.8%) and uveitis (15–19%) was similar across all registers. The proportion of systemic-JIA patients who ever had MAS was lower in Germany (6%) vs UK (15%) and Pharmachild (17%). Conclusion: This analysis is the first and largest to investigate the occurrence of four important comorbidities in three JIA registries in Europe and the role of anti-rheumatic drugs. Combined, these three registries represent one of the biggest collection of cases of JIA worldwide and offer a unique setting for future JIA outcome studies.